An exploratory investigation into the reception of verbal and video feedback provided to players in an Australian Football League club - Mason, R. J.; Farrow, D.; Hattie, J. A. C. (International Journal of Sports Science & Coaching, 2021)
Coach observation studies commonly examine training and competition environments, with little attention paid to the ways in which coaches provide video feedback in a performance analysis setting. In addition, few studies have considered the reception of feedback by an athlete, or the characteristics of the athlete that may support or hinder feedback reception. The purposes of this study were threefold. First, to examine the characteristics of feedback provided by a coach during a typical video feedback meeting. Second, to measure the impact of this feedback on athlete learning. Third, to consider a range of learner characteristics that may impact feedback reception. Six coaches and six players affiliated with an Australian Football League (AFL) club were recruited. Coach-player dyads were observed in one-to-one video feedback meetings following a game played in the 2017 season. Players were interviewed to test feedback recall. Players also completed a series of tests designed to measure learner characteristics, with the intention of discovering moderating factors of the relationship between feedback and learning outcomes. Rates of feedback generally mirrored those found in previous studies. Coaches provided nearly 30 feedback messages during each meeting. Players recalled 50% of summarised feedback messages but just 6% of all feedback a week later. A ceiling effect on learner characteristics was observed. The paper presents a novel design for examining feedback effectiveness while considering learner characteristics. Given the findings on feedback quantity and recall, coaches are encouraged to adopt a `less is more` approach to providing feedback.